Increasing Rigor to More Challenging Cognitive Processes - Lleuvelyn Areglado, Cacha; Abrizah, Abdullah (2018)
This paper highlights the importance of ensuring empirical rigor consistent to the level of emphasis that captured the multiple realities of graduate students’ analytical information processing ability and understanding relevant conception as they heightened critical thinking skills. Assessment tools are required where students are empowered to challenge ideas, authentic searches for complex information problems, and look for workable solutions integrating information technology capabilities. The repeated measures design is one of the more practical ways to detect effect of repeated assessment, change, improved cognitive performance, an outcome that is not due to chance. To corroborate quantitative outcomes from multiple cognitive skills assessments, the researchers used qualitative approaches like open-ended survey questions, critical reflection, interviews and review of learning e-portfolios to verify intellectual efforts that can take place in an innovative way. The activities also served as validity checks between the quantitative outcome and the researchers’ analysis to interact with students’ understanding by allowing them to have a voice through their contextual interactive account of their involvement and cognitive experience during assessment. The students’ qualitative feedback are useful as they have made up for the lack of salient points in the quantitative course of investigation.